Cenozoic climate change and diversification on the continental shelf and slope: evolution of gastropod diversity in the family Solariellidae (Trochoidea). Issue 4 (4th March 2013) - Williams, S. T.; Smith, L. M.; Herbert, D. G.; Marshall, B. A.; Warén, A.; Kiel, S.; Dyal, P.; Linse, K.; Vilvens, C.; Kano, Y.
Abstract: Recent expeditions have revealed high levels of biodiversity in the tropical deep‐sea, yet little is known about the age or origin of this biodiversity, and large‐scale molecular studies are still few in number. In this study, we had access to the largest number of solariellid gastropods ever collected for molecular studies, including many rare and unusual taxa. We used a Bayesian chronogram of these deep‐sea gastropods (1) to test the hypothesis that deep‐water communities arose onshore, (2) to determine whether Antarctica acted as a source of diversity for deep‐water communities elsewhere and (3) to determine how factors like global climate change have affected evolution on the continental slope. We show that although fossil data suggest that solariellid gastropods likely arose in a shallow, tropical environment, interpretation of the molecular data is equivocal with respect to the origin of the group. On the other hand, the molecular data clearly show that Antarctic species sampled represent a recent invasion, rather than a relictual ancestral lineage. We also show that an abrupt period of global warming during the Palaeocene Eocene Thermal Maximum (PETM) leaves no molecular record of change in diversification rate in solariellids and that the group radiated before the PETM. Conversely, there is a substantial, although not significant increase in the rate of diversification of a major clade approximately 33.7 Mya, coinciding with a period of global cooling at the Eocene–Oligocene transition. Increased nutrients made available by contemporaneous changes to erosion, ocean circulation, tectonic events and upwelling may explain increased diversification, suggesting that food availability may have been a factor limiting exploitation of deep‐sea habitats. Tectonic events that shaped diversification in reef‐associated taxa and deep‐water squat lobsters in central Indo‐West Pacific were also probably important in the evolution of solariellids during the Oligo‐Miocene. Abstract : Ilanga laevissima dredged at 100 m off Amanzimtoti, KwaZulu‐Natal (NMSA D4831). Photo credit: D. G. Herbert, KwaZulu‐Natal Museum.